Mitomycin C in the Therapy of Recurrent Esophageal Strictures: Hype or Hope? - Berger, Michael; Ure, Benno; Lacher, Martin (European Journal of Pediatric Surgery, 2012)
Introduction Esophageal strictures refractory to conservative treatment represent a major problem in children. The application of Mitomycin C to the site of stricture has been introduced, but the experience with this novel approach remains very limited.Methods Systematic review of publications on the topical application of Mitomycin C in children with persistent esophageal stricture.Results We identified 11 publications including 31 cases. The underlying cause of stricture was caustic ingestion in 19 (61.2%), esophageal surgery in 7 (22.6%), and others in 5 children (16.2%). The median age of the patients was 48 months (range 4 to 276 months). In the majority of cases cotton pledgets soaked in solution of Mitomycin C were applied endoscopically. Various other techniques such as drug-eluting stents were used. Mitomycin C was applied from 1 to 12 times within intervals from 1 to 12 weeks. The concentrations of Mitomycin C varied considerably between 0.1 and 1 mg/mL. After a mean follow-up time of 22 (6 to 60) months complete relief of symptoms was reported for 21 children (67.7%), and 6 (19.4%) had a partial relief. In four children (12.9%) Mitomycin C treatment failed. No direct or indirect adverse effects were reported.Conclusion The short-term results of topical Mitomycin C application for refractory esophageal stricture reported in the literature are very encouraging. Prospective studies are mandatory to determine the optimal time points, dosage, and modalities of treatment before a recommendation can be given.
Keywords: mitomycin C; esophageal stricture; esophageal stenosis; endoscopy; balloon dilation